Vibrio fischeri Bioassay for determination of toxicity in petroleum contaminated soils from Tropical Southeast Mexico - Adams, Randy H.; Rodríguez, Verónica I. Domínguez; Cruz, Joel Zavala (Universiti Kebangsaan Malaysia, 2015)
Using the Microtox bioassay toxicity was determined in 16 areas located in eight sites: In contaminated areas, in areas with natural recovery, after bioremediation and phytoremediation projects and in control areas (uncontaminated). These areas correspond to the following ecosystems: mangrove, fresh water swamp (Pachira aquatica), marsh and pasture (in the coastal plain and Pliocene-Pleistocene terraces). A significant toxicity was detected in uncontaminated organic soils (22.2-49.1 toxicity units (TU)) which were comparable to levels found in hydrocarbon contaminated areas (22.3- 42.0 TU). Generally, the toxicity in organic soils was much higher than that found in mineral soils (which was from below quantification levels to 9.3 TU). In an area restored by phytoremediation, the simple method used by Petróleos Mexicanos achieved recovery and superficial detoxification in the treated plot, exhibiting a toxicity reduction of 2.4 times with respect to untreated soil and a toxicity even slightly lower than the uncontaminated control in the same ecosystem (22.2 TU). Likewise, a bioremediation project in pasture resulted in a toxicity reduction down to levels comparable to uncontaminated soil (from below quantification levels to 7.9 TU). A tendency to decrease toxicity in organic soils during the rainy season was observed, toxicity drop in 80% of the areas sampled. Based on these findings, recommendations are presented for use of this test method in regional diagnostic studies.